(untitled) (Revista Contexto & Educação, 2025)
The article presents the contributions of Mario Osorio Marques to the Institutional Program of Teaching Initiation Scholarships (PIBID) at the Federal University of Rio Grande (FURG). Writing is highlighted as a formative and epistemological tool, fostering dialogue between theory and practice in teacher education. Materialized in artifacts such as collective portfolios and classroom narratives, writing serves as a means for research and critical reflection. These practices enable program participants to reframe their experiences, investigate their pedagogical practices, and (re)construct knowledge about teaching. Research on these artifacts demonstrates the power of writing as a way of thinking, understanding, and, through this process, becoming a teacher.